An Analysis of Racism in Jason Reynolds and Brendan Kiely’s All American Boys - Siti Mei Rahmadayanti (Faculty Humanities, 2024)
This research focuses on the racism depicted on Black people in the novel All American Boys. Racism in the novel is analyzed by using the theory of genetic structuralism by Lucien Goldmann. By applying the concepts of human facts, collective subject, and significant structures, the discourse of racism in the novel is revealed. These three concepts bridge the understanding of whether the authors agree or disagree with the issue of racism raised in the novel. This research employs a qualitative approach that analyse textual data to explore the portrayal of racism against Black people in a novel. Data collection involves primary data and secondary data. Primary data are taken from the novel and the website and other sources that specifically talk about the contextual background of the novel. Secondary data are taken from articles, books, and online resources for socio-historical context to support the analysis. Data processing includes classifying information on racism using Goldmann’s genetic structuralism, focusing on human facts, collective subject, significant structures, and worldview.
Reupload file Repositori 10 Februari 2026_Kholif/Keysa
Keywords: racism; all american boys; strukturalisme genetic